Competence in medical practice as perceived by Malaysian medical interns: a measurement invariance analysis - Adewale, Abideen Adeyemi; Abd. Manaf, Noor Hazilah; Omar, Azura (International Foundation for Research and Development, 2012)
This study investigates the perception of Malaysian housemen on what the indicators of competence are in the medical practice. This derives from the need for the interns to have the requisite skill needed to make them competent in the post-medical school medical practice. A survey questionnaire was administered on all 2,046 housemen in all medical schools across Malaysia as at April 30, 2008 when data was collected. Data so obtained were subjected to statistical analysis based on N=1213 using both the structural equation modeling via SPSS AMOS 18 software. Nine skills were identified in all. These are interpersonal, IT, patient management, basic, holistic, science, ethics, coping, and clinical skills. While all the skills were found to be statistically significant, no factorial invariance was observed when the data is split into demographic divides.